Potential of city break clubbing tourism in Wrocław - Iwanicki Grzegorz; Dłużewska Anna (Bulletin of Geography. Socio-Economic Series)
Over the last decade Polish cities have become popular destinations of the foreign clubbing tourism. Interest of foreign tourists, however, is not reflected in the interest of scientists, because clubbing tourism-related issues have not been extensively studied in the literature regarding Polish cities. In this paper the authors have tried to fill this gap by analysing the potential of city break clubbing tourism in Wrocław, the city which has been selected the European Capital of Culture 2016. As part of the analysis, the following elements affecting the development of this type of tourism were examined: transport accessibility, clubbing infrastructure (discos, nightclubs and pubs), and other factors (accommodation facilities and selected tourist attractions). The transport accessibility data include only regular direct flights carried by low-cost carriers (LCC) in 2014 (number of connections, frequency of flights and ticket prices), as this type of transportation is crucial for city break tourism.